Non-Coding RNAs and Brain Tumors: Insights Into Their Roles in Apoptosis - Tamtaji, Omid Reza; Derakhshan, Maryam; Rashidi Noshabad, Fatemeh Zahra; Razaviyan, Javad; Hadavi, Razie; Jafarpour, Hamed; Jafari, Ameneh; Rajabi, Ali; Hamblin, Michael R.; Mahabady, Mahmood Khaksary; Taghizadieh, Mohammad; Mirzaei, Hamed (Frontiers in Cell and Developmental Biology, 2022)
A major terrifying ailment afflicting the humans throughout the world is brain tumor, which causes a lot of mortality among pediatric and adult solid tumors. Several major barriers to the treatment and diagnosis of the brain tumors are the specific micro-environmental and cell-intrinsic features of neural tissues. Absence of the nutrients and hypoxia trigger the cells' mortality in the core of the tumors of humans' brains: however, type of the cells' mortality, including apoptosis or necrosis, has been not found obviously. Current studies have emphasized the non-coding RNAs (ncRNAs) since their crucial impacts on carcinogenesis have been discovered. Several investigations suggest the essential contribution of such molecules in the development of brain tumors and the respective roles in apoptosis. Herein, we summarize the apoptosis-related non-coding RNAs in brain tumors.